The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1302/1863-2548.12.170122
|View full text |Cite
|
Sign up to set email alerts
|

Buckling down on torus fractures: Has evolving evidence affected practice?

Abstract: PurposeThe purpose of this study was to evaluate the management of paediatric torus fractures of the distal forearm in current practice in light of growing evidence supporting a ‘minimalist’ approach with splint immobilization and limited follow-up. We hypothesized that ‘traditional’ cast-based management has persisted despite alternative evidence.MethodsA retrospective review was performed of a consecutive series of paediatric patients diagnosed with torus fractures of the distal forearm between 2011 and 2014… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…Many studies have demonstrated that a minimalist approach to managing these fractures, has shown improved function, reduced return time to school along with reduced cost and medical time. 60 , 61 Recent research has guided the use of soft casts or splints rather than rigid casts, 62 and this has been advocated by the most recent National Institute for Health and Care Excellence (NICE) guidelines for the management of torus fractures. 63 A recent retrospective study also demonstrated increased efficiency and cost reduction in managing these injuries in a VFC setting.…”
Section: Paediatric Injuriesmentioning
confidence: 99%
“…Many studies have demonstrated that a minimalist approach to managing these fractures, has shown improved function, reduced return time to school along with reduced cost and medical time. 60 , 61 Recent research has guided the use of soft casts or splints rather than rigid casts, 62 and this has been advocated by the most recent National Institute for Health and Care Excellence (NICE) guidelines for the management of torus fractures. 63 A recent retrospective study also demonstrated increased efficiency and cost reduction in managing these injuries in a VFC setting.…”
Section: Paediatric Injuriesmentioning
confidence: 99%
“…In this way, we are conducting a study about the efficacy of treating children with torus distal radius fractures with an easy-to-use 3D-printed splint in place of the classic plaster cast usually moulded by an orthopaedic specialist and a dedicated nurse. Results collected to date showed faster treatment in the emergency room, improved childhood activities during recovery and high satisfaction for parents and children without any complication or delay in the healing process as seen for splints in previous studies [23,24]. As we can easily expect new epidemic waves in the near future, changing medical care modalities for minor trauma in children (at the moment, the least vaccinated population) could improve our attempts to limit the spread of the virus.…”
Section: Discussionmentioning
confidence: 75%
“…19 Despite these guidelines, there is evidence that there is still a high rate of utilization of casting, frequent follow-up, and serial radiographs, all of which can be potentially harmful to patients. 15,20 Our study demonstrated that while an increasing proportion of orthopaedic providers are managing DRBFx with removable wrist splints and limited follow-up, there remain a substantial number of pediatric orthopaedic surgeons who continue to prefer more aggressive measures. The rationale behind this discrepancy remains unclear.…”
Section: Discussionmentioning
confidence: 85%
“…POSNA guidelines similarly recommend a removable wrist splint with limited follow-up 19. Despite these guidelines, there is evidence that there is still a high rate of utilization of casting, frequent follow-up, and serial radiographs, all of which can be potentially harmful to patients 15,20…”
Section: Discussionmentioning
confidence: 99%